Penerapan modul biologi berorientasi problem based learning untuk meningkatkan hasil belajar kognitif mahasiswa keperawatan - Lisa Fradisa; Kalpana Kartika (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2019)
The low understanding of students in learning biology in cell communication materials. One way to overcome these problems is to apply a problem-based learning-oriented biology module. This study aims to determine the improvement of cognitive learning outcomes of nursing students through the application of problem-based learning oriented biology modules. This type of research is Classroom Action Research conducted 2 cycles. The study was conducted at STIKes Perintis Padang. The subjects of this study were 28 nursing students. The research instrument consisted of observation sheets, student cognitive learning test results, documentation and field notes. Data collection is done by formative tests. Data analysis techniques using descriptive analysis. The results showed that the application of problem based learning oriented biology modules could improve student cognitive learning outcomes with classical completeness from 79% to reach 89% and increase in cognitive learning outcomes into the medium category (N-gain 0.5). Based on these results it can be concluded that the application of problem-based learning-oriented biology modules can improve the cognitive learning outcomes of nursing students.